IS THERE A RELATIONSHIP BETWEEN CORPORATE SOCIAL RESPONSIBILITY AND CORPORATE REPUTATION? EVIDENCE FROM THE CROATIAN NEWSPAPER INDUSTRY - Miroslav Ivić; Marina Lovrinčević; Luka Zovko (Elektronički Zbornik Radova Veleučilišta u Šibeniku)
In order to contribute literature in the field of corporate social responsibility and corporate reputation in the media industry, a survey was conducted on a sample of Croatian companies. Corporate social responsibility was operationalized through the prism of relationships with the owners, employees, customers, suppliers, and the local community. On the other hand, corporate reputation was operationalized using corporate identity and corporate image. Correlation analysis was used to test the relationship between corporate social responsibility and corporate reputation. The results suggest that there is a significant, strong, and positive relationship between the implementation of the corporate social responsibility practice and both corporate identity and corporate image so the main hypothesis could be accepted.